PRODUCTION OF ROTARY ENGINES’ PARTS FROM ALUMINUM ALLOYS USING LOST FOAM CASTING PROCESS - E. I. Marukovich; A. M. Branovitskiy; A. A. Kruglov; V. A. Dement’ev; N. P. Sadovskiy (Литьë и металлургия, 2018)
The production technology of casting details for rotary engine from the aluminum alloy АК12М2 is developed. The bulk density of expanded polystyrene to ensure the best quality of the surface of castings has been experimentally established. The lost foam casting shop was organized in the experimental department of the Institute.